Daily activity, diet and habitat of Bali myna (Leucopsar rothschildi) in Nusa Penida, Bali, Indonesia (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Sudaryanto FX, Pudyatmoko S, Djohan TS, Subagja J, Suana IW, Kalih LATTWS, Hardini J, Subagio J. 2020. Daily activity, diet, and habitat of Bali myna (Leucopsar rothschildi) in Nusa Penida, Bali, Indonesia. Biodiversitas 21: 4474-4482. Endemic Bali myna (Leucopsar rothschildi) has a very high risk of extinction in its natural habitat. Bali Barat National Park (BBNP) and other NGO's have conducted various conservation activities, such as breeding and release, community development, environmental improvement, and awareness program. Breeding and release have already been applied in Nusa Penida out of its original habitat. To support the conservation of Bali myna, basic ecological data are needed, eg. daily activities, habitat profile, home range, and interspecific interaction. This study aimed to meet the needs of these vegetation profiles. We collected data from 2013 to 2015. Daily activities were observed on a couple of Bali myna in a nest box at agroforestry area. Habitat profile was determined by analyzing vegetation at their foraging, nesting, and resting areas, using a quadrate plot of 20 x 20 m2. To estimate the home range, of the Bali myna, we recorded 700 points of perching of these birds, by using Global Positioning System, and analyzed using Convex Polygon Method. Their interaction with other animals was carried out at their foraging, nesting, and roosting areas. Daily activities of the Bali myna in Nusa Penida are predominantly recorded in agroforestry areas, so its home range is relatively narrow, at 3.9 ha. The food types of Bali myna in Nusa Penida were fruits, insects, and nectar flowers. Sucking on nectar flower is the first report here. The vegetation profile of nesting and foraging area for Bali myna consists of one layer of thick and dense canopy, while the vegetation profile of resting area is not too dense, which is composed of two canopy layers. Bali myna's interactions with other animals for competition, predation, and mutualistic symbiosis. These data are expected to be used to make decisions in order to conserve Bali myna in Nusa Penida.
Keywords: Bali myna, daily activity, habitat profile, home range, interspecific interaction